Crack propagation analysis of reinforced concrete members - Gunasekera, Amarasena Wickramaratna; Tanabe, Tada-Aki; Pama, Ricardo P.; Scott, David; Government of Canada (Bangkok : Asian Institute of Technology, 1977)
Crack propagation analysis of reinforced concrete members was done using finite element method. An attempt was made to incorporate the nonlinear behaviour of material properties and most important, the bond slip and its softening was taken into account using joint element which has zero thickness. Combining with this the laminar discretization, the displacement of steel could be differentiated from that of concrete at the same location in the plan. A reinforced concrete beam, subjected to crack propagation, under an increasing central load, was analysed and the results obtained was in agreement with the experimentally obtained results. Also, as an example for extended application of the method, an anchor bolt anchorage in reinforced concrete with two different support conditions was analyzed to demonstrate how proper reinforcement is decided for complicated situations through this method.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Reinforced concrete -- Cracking